Economics of production of Sunkagati-1 variety of acid lime in Nepal - Subedi, Sanjiv; Timsina, Krishna Prasad (Journal of Nepal Agricultural Research Council, 2023)
There is a huge opportunity for acid lime farming in Nepal. The demand is much higher than domestic production resulting voluminous import from abroad. This research aimed to assess the economics of production of Sunkagati-1 variety of acid lime in Nepal. Morang, Sunsari, Chitwan and Nawalparasi districts were selected for this study after consultation with the concerned agricultural experts and nursery entrepreneurs producing Sunkagati-1 saplings. The primary information was collected through the field survey whereas secondary information was obtained reviewing the relevant literatures. All total 70 farmers were selected as the samples through simple random sampling for the field survey. Financial analysis of farms with plant age between 3 to 7 years, was carried out which estimated the NPV (12% discount rate) NRs.4,48,672/ha, BCR 1.09, IRR 19% and the Pay-back period of 5 years, 5 months and 26 days. The value of BCR being greater than one, IRR higher than discount rate, positive NPV and short payback period indicated that commercial acid lime farming cultivating Sunkagati-1 variety is a profitable enterprise in Nepal. The unpaired t-test showed that there is no significant difference in productivity of Sunkagati-1 across eastern (Sunsari and Morang) and central (Chitwan and Nawalpur) regions; however, the price of acid lime in central region (NRs.102/kg) was significantly higher (1 % level of significance) than that of in eastern (NRs.93.8/kg). Moreover, this study revealed that porous border and unorganized market (I= 0.81) was the most severe problem followed by infestation of disease and insect pests (I= 0.76), inadequate quality seedlings (I= 0.68), inadequate technical knowledge and trainings (I=0.41) and inadequate storage and processing facilities (0.34). There is need of government intervention which would assure access to quality inputs & technology, marketing & value chain development and appropriate plant protection measures for the promotion of commercial acid lime farming in Nepal.